2020
DOI: 10.1186/s13075-020-02203-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the pulmonary arteries in patients with Takayasu arteritis: a prospective study from a single centre in China

Abstract: Background: Takayasu arteritis (TA) is a large vessel vasculitis that can involve pulmonary arteries (PAs). We studied multiple clinical characteristics related to pulmonary artery involvement (PAI) in TA patients. Methods: We enrolled 216 patients with TA from a large prospective cohort. PAI was assessed in each patient based on data from magnetic resonance angiography/computed tomography angiography. Pulmonary hypertension, cardiac function, and pulmonary parenchymal lesions were evaluated further in patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 33 publications
4
18
0
14
Order By: Relevance
“…The effect of PAI has not been fully elucidated. PAI is reported with TAK in 5.7 to 25.93 % (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In this study, the presence of PAI was 14.6 %, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of PAI has not been fully elucidated. PAI is reported with TAK in 5.7 to 25.93 % (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In this study, the presence of PAI was 14.6 %, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Vessel wall in ammation leads to arterial wall thickening, dilation, stenosis and occlusion. PA involvement (PAI) occurs in 5.7-25.93 % of all cases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). TAK with PAI is occasionally complicated with pulmonary hypertension (PH), resulting in the risk of early mortality (8, 11).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that inflammation may spread to the peripheral pulmonary artery wall, resulting in micropulmonary infarction, alveolar hemorrhaging, and fibrin deposited during the healing process, leading to organizing pneumonia. In some cases of Takayasu arteritis, biopsy results of the pneumonia-like lesions indicated hemorrhagic infarction accompanied by fibrinoid necrosis of the small vessels and infiltration of inflammatory cells ( 3 ). In the current case, we found inflammatory wall thickening and stenosis in the proximal part of the left lower lobe pulmonary artery but no evidence of vasculitis in the peripheral part.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory symptoms appear in approximately 10.8% of patients with Takayasu arteritis ( 1 ). Recently, it has been reported that 6.3% to 25.9% of patients have pulmonary artery involvement ( 2 , 3 ). In Takayasu arteritis, pulmonary artery involvement sometimes causes respiratory symptoms without visible pulmonary artery stenosis, pulmonary artery infarction, or pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Few data are available on ultrasound-based assessment of cardiac function in large vessel vasculitis, although features of early cardiac involvement have been described in other autoimmune diseases [13,14]. Nevertheless, an increase in left ventricular mass [15] and indirect involvement of the right ventricle, secondary to pulmonary hypertension, have been detected by echocardiography in TAK patients [16]. Thus, as with several other diseases associated with inflammatory features in the arterial wall, such as hypertension and atherosclerosis [17,18] and oxidative stress [18,19], changes in cardiac structure and function may characterize the progression of TAK disease, increasing the overall risk of cardiovascular morbidity/mortality [20,21].…”
Section: Introductionmentioning
confidence: 99%